Spliceosomal snRNA Epitranscriptomics - Morais, Pedro; Adachi, Hironori; Yu, Yi-Tao (Frontiers in Genetics, 2021)
Small nuclear RNAs (snRNA) are critical components of the spliceosome that catalyzes the splicing of pre-mRNA. snRNAs are each complexed with many proteins to form RNA-protein complexes, termed small nuclear ribonucleoproteins (snRNPs), in the cell nucleus. snRNPs participate in pre-mRNA splicing by recognizing the critical sequence elements present in the introns, thereby forming active spliceosomes. The recognition is achieved primarily by base-pairing interactions (or nucleotide-nucleotide contact) between snRNAs and pre-mRNA. Notably, snRNAs are extensively modified with different RNA modifications, which confer unique properties to the RNAs. Here we review the current knowledge of the mechanisms and functions of snRNA modifications and their biological relevance in the splicing process.